Backward running: The why and how to program for better athleticism - Uthoff, A.; Oliver, J.; Cronin, J.; Winwood, P.; Harrison, C. (Strength and Conditioning Journal, 2019)
Backward running (br) is a common locomotive technique used by most overground athletes during both competition and training, yet there are limited empirically based recommendations for using br training for athletes. This article highlights the role of br in sports context, provides insights into why br may benefit athletes, and recommends how to integrate br into strength and conditioning programs. Informed guidance is provided on the practical applications for athletes, which should help speed and strength coaches design and facilitate br in a safe and progressively overloaded fashion for youth and adult athletes alike.